2016
DOI: 10.12806/v15/i4/c2
|View full text |Cite
|
Sign up to set email alerts
|

Finding What Works: Leadership Competencies for the Changing Healthcare Environment

Abstract: Individuals expected to offer leadership are often chosen based on their power position within the field of interest and specialization in the context area being addressed and not on their leadership style. Leadership education curriculum often focuses on change as a product of leadership and leadership styles but places little emphasis on how the leadership styles of those chosen to lead change can influence the change process. In order to inform the development of curriculum targeting this aspect of leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Leadership skills and behaviours were identified that included leading by example; developing and exhibiting a transformational leadership style; and the ability to communicate the organisation mission. The ability to develop oneself and others was also identified in studies (Citaku et al, 2012;Connelly et al, 2003;Furukawa and Cunha, 2011;Palarca et al, 2008;Herd et al, 2016;Liang et al, 2013;Liang et al, 2018). Management ability to be proactive towards clinical and organisational change was also deemed relevant by some researchers (O'Neil et al, 2008;Sherman et al, 2007;Palarca et al, 2008;Herd et al, 2016;Liang et al, 2013;Hazelbaker, 2013;Liang et al, 2018).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Leadership skills and behaviours were identified that included leading by example; developing and exhibiting a transformational leadership style; and the ability to communicate the organisation mission. The ability to develop oneself and others was also identified in studies (Citaku et al, 2012;Connelly et al, 2003;Furukawa and Cunha, 2011;Palarca et al, 2008;Herd et al, 2016;Liang et al, 2013;Liang et al, 2018). Management ability to be proactive towards clinical and organisational change was also deemed relevant by some researchers (O'Neil et al, 2008;Sherman et al, 2007;Palarca et al, 2008;Herd et al, 2016;Liang et al, 2013;Hazelbaker, 2013;Liang et al, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Health-care reforms are underway in many countries and regions; often embracing new managerial models (Pihlainen et al, 2016). Knowledge of the health-care system featured as an important competency in many studies reflecting the need for managers to keep pace with health-care reform and understand the significance of these reforms for their own organisation (Hennessy and Hicks, 2003;Herd et al, 2016;Berkenbosch et al, 2013;Hazelbaker, 2013;Liang et al, 2018). Liang et al (2013Liang et al ( , 2018 discuss the importance of evidence based informed decision-making that can positively impact the quality and effectiveness of management decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership competencies include skills and behaviors that contribute to superior organizational performance. Organizations are better placed in the marketplace if they focus on developing their next generation of leaders (Herd, Adams‐Pope, Bowers, & Sims, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that managers have a significant role in promoting health systems. The scientific community in the field of health should seek to define and identify the competencies needed for managers, especially hospital managers (12).…”
Section: Introductionmentioning
confidence: 99%